Development and optimization of an intergeneric conjugation system and analysis of promoter activity in Streptomyces rimosus M527 - Song, Zhang-qing; Liao, Zhi-jun; Hu, Ye-feng; Ma, Zheng; Bechthold, Andreas; Yu, Xiao-ping (Journal of Zhejiang University. B. Science, 2019)
An efficient genetic transformation system and suitable promoters are essential prerequisites for gene expression studies and genetic engineering in streptomycetes. In this study, firstly, a genetic transformation system based on intergeneric conjugation was developed in Streptomyces rimosus M527, a bacterial strain which exhibits strong antagonistic activity against a broad range of plant-pathogenic fungi. Some experimental parameters involved in this procedure were optimized, including the conjugative media, ratio of donor to recipient, heat shock temperature, and incubation time of mixed culture. Under the optimal conditions, a maximal conjugation frequency of 3.05×10 -5 per recipient was obtained. Subsequently, based on the above developed and optimized transformation system, the synthetic promoters SPL-21 and SPL-57, a native promoter potrB , and a constitutive promoter permE" commonly used for gene expression in streptomycetes were selected and their activity was analyzed using gusA as a reporter gene in S. rimosus M527. Among the four tested promoters, SPL-21 exhibited the strongest expression activity and gave rise to a 2.2-fold increase in (3-glucuronidase (GUS) activity compared with the control promoter permE *. Promoter SPL-57 showed activity comparable to that of permE *. Promoter potrB , which showed the lowest activity, showed a 50% decrease in GUS activity compared with the control permE *. The transformation system developed in this study and the tested promotors provide a basis for the further modification of S. rimosus M527.